Hubungan Dukungan Keluarga Dengan Kebugaran Jasmani Lansia Di Kecamatan Denpasar Barat Tahun 2019 - I Nyoman Tripayana (JURNAL MEDIKA USADA, 2020)
Background and goals: People who are getting older will reduce their ability to perform daily physical activities that can affect their physical fitness. Family support is needed by the elderly in living their old age because the family plays an important role and has the responsibility in caring for the elderly. Good family support for elderly activities will be able to maintain and improve the health and fitness of the elderly. This study aims to determine the relationship of family support with physical fitness of the elderly.Method: This study used a cross sectional design involving 96 elderly samples that met the requirements. Data collection is done by testing and filling out questionnaires. Data were analyzed using the Spearman Rho test and binary logistic regression test.Results: Bivariate analysis showed that variables related to physical fitness were family support (p = 0.004), gender (p = 0.035) and work status (p = 0.001). The results of multivariate analysis showed that variables related to physical fitness were family support (AOR 5,618; 95% CI: 1,624-19,435) and work status (AOR 10,974; 95% CI: 2,452-49,095).Conclusion: Family support has a relationship with elderly physical fitness. Characteristics of work status samples have a relationship with physical fitness of the elderly. The family should always provide positive support to the elderly in fulfilling daily activities in accordance with the ability of the elderly in their effort to maintain and improve the physical fitness of the elderly.